Techno-economic evaluation of biofuels production from RBDPO using metal with zeolite support as strategies to end crude oil dependence - Sayekti Kurniati (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2026)
Background: The production of sustainable aviation fuel and bio gasoline from refined bleached degummed palm oil (RBDPO) has attracted increasing attention as a strategy to support low-carbon energy development. However, due to the complexity of the liquid product composition, determining the dominant reaction pathways and evaluating the technical and economic feasibility of the process remain challenging. This study aims to evaluate the techno-economic feasibility of hydrodeoxygenation of RBDPO under atmospheric to intermediate pressure conditions. Methods: The process technology was developed based on mass and energy balances and financial modelling. Atom mass balance combined with error minimization was applied to identify the dominant reaction pathways, Process simulations were performed using Aspen HYSYS, while laboratory data were used as the basis for economic evaluation. Equipment costs were estimated using Aspen Capital Cost Estimator to determine the total capital investment. Findings: The results indicate that several reactions occur during biofuel (bioavtur and bio gasoline) production, including hydrodeoxygenation, hydro decarboxylation, cracking, and polymerization. A standalone bioavtur plant requires a capital expenditure (CAPEX) of approximately USD 87,775,899 and an operating expenditure (OPEX) of USD 6,487,559, assuming an exchange rate IDR 15,500 per USD. The financial analysis yields an Internal Rate of Return (IRR) of 12.59% and a Net Present Value (NPV) of IDR 685,679,000,000. In comparison, a bio gasoline plant requires a lower CAPEX of USD 75,256,210 and an OPEX of USD 5,944,681 under the same exchange rate. Furthermore, it demonstrates better financial performance, with an IRR of 15.46% and a NPV of IDR 346,690,000,000. Conclusion: The results demonstrate that hydrodeoxygenation of RBDPO is technically feasible and economically viable under atmospheric to intermediate pressure conditions. These findings provide a practical basis for developing commercially competitive bioavtur and bio gasoline production systems. Novelty/Originality of this article: This study combines reaction pathways analysis and techno-economic evaluation of RBDPO hydrodeoxygenation for sustainable biofuel production.